PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH, DAN MUSYARAKAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA TAHUN 2010-2014 - B01111033, Rima Pratama (Jurnal Pembangunan dan Pemerataan, 2017)
AbstractThis study aims to determine the effect of murabaha financing, Musharaka andmudaraba to profitability Bank Syariah period 2010-2014. The results of this study indicatethat the financing murabaha proxied by Return on Assets (ROA) positive effect on theprofitability of Islamic banks in Indonesia. Financing profit and loss sharing negative effect onthe profitability of Islamic banks in Indonesia. Negative effect on profit and loss sharingfinancing indicates that the financing provided is still productive and still less enthusesmudharabah and musyarakah on Islamic banking.Keywords: ROA (Return on Assets), Murabaha, Mudharabah, Musharaka.